2022
DOI: 10.3390/biology11101406
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Protects against Colon Pathology via p53 and May Be a Biomarker for Colon Cancer Progression

Abstract: Previous observations made in human and mouse colons suggest that reelin protects the colon from pathology. In this study, we evaluated reelin expression during the transition from either colitis or precancerous lesions to colon cancer and tried to elucidate reelin regulation under these transition processes. Samples of healthy and pathological colons from humans and mice treated with either azoxymethane/dextran sulfate sodium (DSS) or azoxymethane alone were used. The relative abundances of reelin, DNMT-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In a recent study, it was stated that an increase in reelin prevents the development of colon cancer, and its decrease might trigger the formation of colon carcinoma, and it was suggested as a biomarker in the prediction of prognosis. [14] In the present study, it was found that reelin was more expressed in papillary RCC, but the expression decreased in clear cell carcinoma, which is a more aggressive tumor, compared to papillary RCC, and the difference between them was statistically significant. Decreased expression of reelin in clear cell RCC, which is quite aggressive, is a finding that was expected, and it was in line with the literature data.…”
Section: Discussionsupporting
confidence: 42%
“…In a recent study, it was stated that an increase in reelin prevents the development of colon cancer, and its decrease might trigger the formation of colon carcinoma, and it was suggested as a biomarker in the prediction of prognosis. [14] In the present study, it was found that reelin was more expressed in papillary RCC, but the expression decreased in clear cell carcinoma, which is a more aggressive tumor, compared to papillary RCC, and the difference between them was statistically significant. Decreased expression of reelin in clear cell RCC, which is quite aggressive, is a finding that was expected, and it was in line with the literature data.…”
Section: Discussionsupporting
confidence: 42%
“…These are common risk factors for cardiovascular disease [130][131][132][133][134][135], pulmonary hypertension [136][137][138][139][140][141][142][143], and stroke [130], of which Reelin lowering could predictably affect in a favorable manner. However, the literature reveals a multifaceted role for Reelin in cancer development [41], with studies suggesting both promotional [144][145][146][147][148][149][150][151][152][153] and inhibitory [62,[154][155][156][157][158][159] effects on malignant cell behavior depending on the cell type and affected organ. Therefore, dedicated studies should assess whether cancer might represent a medical contraindication for future anti-Reelin therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Reelin is also abundant in the blood with a typical concentration of around 10 ng/mL in humans [53], and exercises function outside of the CNS [51,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. In the past 10 years, three major non-neuronal functions for plasma Reelin have been described in inflammation, vascular tone regulation, and thrombosis.…”
Section: Introductionmentioning
confidence: 99%